An Analysis of Students’ English Vocabulary Mastery Based on Nation’s Theory: Identifying Areas of Strengths and Weakness - Marta, Rahayu Nimas; Ardi, Havid (Universitas Negeri Padang, 2025)
This research aims to analyze the vocabulary mastery of seventh-grade students at MTsN 3 Solok Selatan based on Nation’s theory, which includes three aspects: form, meaning, and use. The participants were 30 students from class VII.1 selected through purposive sampling. The vocabulary test consisted of 30 questions, with 10 items for each aspect. This study used a quantitative descriptive method to measure students’ mastery levels. The results showed that the average score in the form aspect was 53.67%, in the meaning aspect was 52.33%, and in the use aspect was 49.33%. These findings indicate that students are more familiar with the form of words, such as spelling and pronunciation, but still struggle to understand word meanings and use them correctly in context. The lowest achievement was found in the use aspect, suggesting that students need more practice in applying vocabulary in real communication. Based on the results, it is recommended that teachers use teaching strategies that integrate form, meaning, and use, such as puzzles, games, and contextual speaking tasks to improve students’ vocabulary mastery. Future researchers are encouraged to explore effective vocabulary learning methods to support students’ improvement, especially in the use aspect.